ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYALURAN KREDIT UMKM (STUDI PADA BANK UMUM KONVENSIONAL YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2022) - Dwi Fatmi Hartini; Ni Nyoman Yuliati; Rusli Amrul (Akuntabel: Jurnal Ilmiah Akuntansi, 2023)
This study aims to examine the factors that influence MSME lending to conventional commercial banks listed on the Indonesia Stock Exchange for the 2018-2022 period. The research method used in this study is a quantitative method with an associative approach. The research variables consist of 5 independent variables, namely non performing loan, capital adequacy ratio, loan to deposit ratio, third party funds, and interest rates and 1 dependent variable, namely lending. This study uses secondary data in the form of annual financial reports from conventional commercial banks published on the Indonesia Stock Exchange for the 2018-2022 period and interest rate data set by Bank Indonesia for the 2018-2022 period on the Central Bureau of Statistics website. Sampling technique using purposive sampling so that a sample of 23 conventional commercial banks was obtained. The analytical method used is multiple linear regression analysis. The test results show that partially non performing loan, loan to deposit ratio, third party funds, interest rates have a positive and significant effect on lending. Capital adequacy ratio no significant effect on lending.